Biphasic cell cycle defect causes impaired neurogenesis in down syndrome - Sharma, Vishi; Nehra, Sunita; Do, Long H.; Ghosh, Anwesha; Deshpande, Aniruddha J.; Singhal, Nishant (Frontiers in Genetics, 2022)
Impaired neurogenesis in Down syndrome (DS) is characterized by reduced neurons, increased glial cells, and delayed cortical lamination. However, the underlying cause for impaired neurogenesis in DS is not clear. Using both human and mouse iPSCs, we demonstrate that DS impaired neurogenesis is due to biphasic cell cycle dysregulation during the generation of neural progenitors from iPSCs named the “neurogenic stage” of neurogenesis. Upon neural induction, DS cells showed reduced proliferation during the early phase followed by increased proliferation in the late phase of the neurogenic stage compared to control cells. While reduced proliferation in the early phase causes reduced neural progenitor pool, increased proliferation in the late phase leads to delayed postmitotic neuron generation in DS. RNAseq analysis of late-phase DS progenitor cells revealed upregulation of S phase-promoting regulators, Notch, Wnt, Interferon pathways, and REST, and downregulation of several genes of the BAF chromatin remodeling complex. NFIB and POU3F4, neurogenic genes activated by the interaction of PAX6 and the BAF complex, were downregulated in DS cells. ChIPseq analysis of late-phase neural progenitors revealed aberrant PAX6 binding with reduced promoter occupancy in DS cells. Together, these data indicate that impaired neurogenesis in DS is due to biphasic cell cycle dysregulation during the neurogenic stage of neurogenesis.